Factors Related to Women of Childbearing Age (WUS) Participation in Performing a Visual Inspection of Acetic Acid (IVA) Pamulang Health Center in 2022 - Siti Nurjanah; Bunga Tiara Carolin; Nurul Husnul Lail (KHD-Production, 2022)
Cervical cancer is the fourth most common type of cancer in women. One of the prevention efforts is by using the IVA test method. The results of the preliminary study at the Pamulang Health Center were only 29 women who took the IVA test and 5 of them were detected positive. This study aimed to determine the factors related to the participation of WUS in conducting early detection of cervical cancer using the IVA test method at Pamulang Health Center in 2022. The design used was a Quantitative analytical research with a cross-sectional approach. The sampling technique was purposive sampling as many as 335 people. Bivariate analysis using Chi-Square test. The results of the univariate study WUS have good knowledge 52.2%, negative attitude 56.1%, get information 67.5%, lack of husband support 57.3%, support from health workers is good 74.3%, access to health services close to 87.8%, had no history of sexually transmitted diseases 60.6% and did not perform early detection of cervical cancer with the IVA method 60.0%. The results of the bivariate study showed that there was a relationship between knowledge (p=0.000, OR=18.632), attitude (p=0.000, OR=3,299), sources of information (p=0.000, OR=5.331), husband's support (p=0.000, OR=2.621), support from health workers (p=0.000, OR=9.988), history of sexually transmitted diseases (p=0.000, OR=4.250), and there was no relationship between access to health services (p=0.973). Knowledge has a high chance of participating in WUS doing IVA. It is hoped that health workers will help increase knowledge and motivate WUS in conducting IVA.